1989
DOI: 10.1007/bf00017450
|View full text |Cite
|
Sign up to set email alerts
|

Limited chloroplast gene transfer via recombination overcomes plastomegenome incompatibility between Nicotiana tabacum and Solanum tuberosum

Abstract: Green cybrids with a new nucleus-chloroplast combination cannot be selected after protoplast fusion in the intersubfamilial Nicotiana-Solanum combination. As an approach to overcome the supposed plastomegenome incompatibility, a partial plastome transfer by genetic recombination has been considered. After fusions of protoplasts of a light-sensitive Nicotiana tabacum (tobacco) plastome mutant and lethally irradiated protoplasts of wild-type Solanum tuberosum (potato), a single green colony was recovered among 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(36 citation statements)
references
References 38 publications
0
35
0
1
Order By: Relevance
“…Although plastid DNA recombination is a frequent phenomenon in the green alga Chlamydomonas (Lemieux etal., 1981), higher plants with stably exchanged plastid genes have only been produced through stringent cell selection for genetic complementation after protoplast fusion (Medgyesy et a/., 1985a). In distant species combinations, where the entire plastome is non-functional with an alien nucleus, a limited plastid gene transfer by recombination has been able to overcome this incompatibility, offering a genetic tool to identify genes crucial in plastid-nucleus co-operation (Thanh and Medgyesy, 1989). These results have also demonstrated that in higher plants the high number of plastid DNA (ptDNA) copies in a plastid, and plastids in a cell, does not hamper the production of a stable and uniform plastome population of new genetic composition, provided segregation is directed by a suitably stringent selection pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although plastid DNA recombination is a frequent phenomenon in the green alga Chlamydomonas (Lemieux etal., 1981), higher plants with stably exchanged plastid genes have only been produced through stringent cell selection for genetic complementation after protoplast fusion (Medgyesy et a/., 1985a). In distant species combinations, where the entire plastome is non-functional with an alien nucleus, a limited plastid gene transfer by recombination has been able to overcome this incompatibility, offering a genetic tool to identify genes crucial in plastid-nucleus co-operation (Thanh and Medgyesy, 1989). These results have also demonstrated that in higher plants the high number of plastid DNA (ptDNA) copies in a plastid, and plastids in a cell, does not hamper the production of a stable and uniform plastome population of new genetic composition, provided segregation is directed by a suitably stringent selection pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic manipulation of the plastid genome in higher plants either by recombination (Medgyesy et a/., 1985a;Thanh and Medgyesy, 1989) or transformation (Staub and Maliga, 1992;Svab eta/., 1990) is in its infancy; in addition to enlargement of the marker pool (Cseplo et a/., 1988) it needs an extension and improvement of the available methods to match the efficiency of the well-established nuclear gene transfer techniques. The present paper demonstrates that a simple PEG-mediated DNA uptake by protoplasts is also suitable to generate stable chloroplast DNA transformants.…”
Section: Spectinomycin Resistance Mutations Can Appear In At Leastmentioning
confidence: 99%
“…Consequently, strictly uniparental inheritance is probably not as common as is generally believed. The inheritance of mtDNA in interspecific crosses of mice was believed to be strictly uniparental (9) until a more sensitive technique (PCR amplification) was used to detect low levels of paternal mtDNA (10 (19,20), showing that chloroplast genes can recombine; the extreme scarcity of detectable recombination in crosses is probably due to a very low frequency of chloroplast fusion. No recombinants of the male and female mitochondrial lineages in blue mussel have been found, even though both genomes have been present in the fertilized egg and germ line cells of embryos in every generation (7,8) for over five million years (21,22).…”
Section: Geneticsmentioning
confidence: 99%
“…Evidence for chloroplast DNA recombination is extensive in the unicellular green alga Chlamydomonas (Lemieux et al, 1988;Boynton et al, 1991). In higher plants, recombination between chloroplast genomes has been demonstrated after protoplast fusion of different genetic lines (Medgyesy et al, 1985;Thanh and Medgyesy, 1989). Moreover, in transformation experiments, homologous donor DNA appears to integrate stably into the plastome by recombination (Svab et al, 1990).…”
mentioning
confidence: 99%